One-Pot Self-Condensation of Phenylboronic Acid with Phenols and Aldehydes - Sharifi, Ali; Saeed Abaee, M.; Mirzaei, Mojtaba; Reza Naimi-Jamal, M. (Asian Journal of Chemistry, 2010)
An efficient procedure is developed for additive-free condensation of boronic acid with phenols and various aromatic and aliphatic aldehydes under solvent-free conditions.